Comment on 'Electron acoustic super solitary waves in a magnetized plasma', J. Plasma Phys. 84, 905840406 (2018). (February 2019) - Verheest, Frank; Hellberg, Manfred A.
Abstract : The plasma model used in a recent paper by Kamalam et al. ( J. Plasma Phys., vol. 84, 2018, 905840406) assumes a Boltzmann description for two hot ion species, in the presence of two adiabatic (fluid) electron species, for the study of obliquely propagating acoustic-type nonlinear solitary waves with respect to a static magnetic field. We argue that the assumption of Boltzmann distributions for the hot ions is incorrect, thus invalidating their conclusions, in particular about the possible occurrence of supersolitons in magnetized plasmas.